Зв'язок - Ozirna, Zhanna (Ukraine Germany, 2018)
Your family can accept that you’re not like others. But could you accept that your family is normal? It’s a story of one coming out that has lasted for a year.
Verzio Film Festival Submission
Keywords: Documentary films